Aryne‐Induced Novel Tandem 1, 2‐Addition/(3+2) Cycloaddition to Generate Imidazolidines and Pyrrolidines1. Issue 34 (3rd July 2015) - Swain, Sharada P.; Shih, Yi‐Chun; Tsay, Shwu‐Chen; Jacob, Joby; Lin, Chun‐Cheng; Hwang, Kuo Chu; Horng, Jia‐Cherng; Hwu, Jih Ru
Abstract A new "single‐flask" method was developed for the synthesis of imidazolidines and pyrrolidines with high stereoselectivity. First, a Schiff base was arylated with an aryne. Second, an intramolecular proton transfer took place from the methylene position to the anionic aryne ring. Third, the resultant ylide reacted with a second equivalent of the same Schiff base in situ or an electron‐deficient alkene through a (3+2) cycloaddition. These sequential tandem 1, 2‐addition/(3+2) cycloaddition reactions led to the desired heterocycles in 63–88 % yields.